Efficacy, durability, and safety of intravitreal faricimab up to every 16 weeks for neovascular age-related macular degeneration (TENAYA and LUCERNE): two randomised, double-masked, phase 3, non-inferiority trials. Issue 10326 (19th February 2022) - Heier, Jeffrey S; Khanani, Arshad M; Quezada Ruiz, Carlos; Basu, Karen; Ferrone, Philip J; Brittain, Christopher; Figueroa, Marta S; Lin, Hugh; Holz, Frank G; Patel, Vaibhavi; Lai, Timothy Y Y; Silverman, David; et al.
Summary: Background: Faricimab is a bispecific antibody that acts through dual inhibition of both angiopoietin-2 and vascular endothelial growth factor A. We report primary results of two phase 3 trials evaluating intravitreal faricimab with extension up to every 16 weeks for neovascular age-related macular degeneration (nAMD). Methods: TENAYA and LUCERNE were randomised, double-masked, non-inferiority trials across 271 sites worldwide. Treatment-naive patients with nAMD aged 50 years or older were randomly assigned (1:1) to intravitreal faricimab 6·0 mg up to every 16 weeks, based on protocol-defined disease activity assessments at weeks 20 and 24, or aflibercept 2·0 mg every 8 weeks. Randomisation was performed through an interactive voice or web-based response system using a stratified permuted block randomisation method. Patients, investigators, those assessing outcomes, and the funder were masked to group assignments. The primary endpoint was mean change in best-corrected visual acuity (BCVA) from baseline averaged over weeks 40, 44, and 48 (prespecified non-inferiority margin of four letters), in the intention-to-treat population. Safety analyses included patients who received at least one dose of study treatment. These trials are registered with ClinicalTrials.gov (TENAYA NCT03823287 and LUCERNE NCT03823300 ). Findings: Across the two trials, 1329 patients were randomly assigned between Feb 19 and Nov 19, 2019 (TENAYA n=334 faricimab and n=337 aflibercept), and between March 11 and Nov 1, 2019 (LUCERNE n=331 faricimab and n=327 aflibercept). BCVA change from baseline with faricimab was non-inferior to aflibercept in both TENAYA (adjusted mean change 5·8 letters [95% CI 4·6 to 7·1] and 5·1 letters [3·9 to 6·4]; treatment difference 0·7 letters [−1·1 to 2·5]) and LUCERNE (6·6 letters [5·3 to 7·8] and 6·6 letters [5·3 to 7·8]; treatment difference 0·0 letters [–1·7 to 1·8]). Rates of ocular adverse events were comparable between faricimab and aflibercept (TENAYA n=121 [36·3%] vs n=128 [38·1%], and LUCERNE n=133 [40·2%] vs n=118 [36·2%]). Interpretation: Visual benefits with faricimab given at up to 16-week intervals demonstrates its potential to meaningfully extend the time between treatments with sustained efficacy, thereby reducing treatment burden in patients with nAMD. Funding: F Hoffmann-La Roche.